A Scientific Approach with PBL Methods to Increase Learning Participation in Sociology Lessons - Ambariyah, Miftahul; Imran, Imran; Wijaya, Tri; Khan, Md Rizwan (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This research aims to address the low learning participation of grade XII Sociology TL 3 students at SMA Negeri 1 Pontianak by implementing a Problem-Based Learning (PBL) model combined with a scientific approach. The study, conducted as Classroom Action Research (CAR), was carried out in two cycles with 38 students. The research problem was identified through preliminary observations, revealing that students were passive, rarely asked questions, and exhibited low engagement during sociology lessons. Data collection techniques included classroom observations, which were used to measure student participation based on scientific approach indicators (observing, questioning, collecting information, reasoning, and communicating) and learning participation indicators (expressing opinions, answering questions, asking questions, providing arguments, and completing assignments). The findings showed that student participation increased from 64.8% in the first cycle to 89.4% in the second cycle, achieving the research performance target of â‰¥80%. This improvement was due to additional treatments in the second cycle, including optimizing group collaboration by assigning specific roles (discussion leader, recorder, presenter, and questioner) to ensure each student had clear responsibilities. Additionally, teachers provided more active guidance, used more relevant and engaging learning media, and facilitated deeper discussions to enhance student interaction. The results confirm that the integration of PBL and the scientific approach effectively increases student participation, fosters critical thinking, and creates an interactive and collaborative learning environment in sociology lessons.